2023
DOI: 10.1515/opag-2022-0174
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and chemical composition of black velvet tamarind (Dialium guineense Willd) and its influence on animal production: A review

Abstract: The world population is expected to double by 2050, creating a greater demand for animal protein sources. This calls for an increase in the supply of animal-derived foods in order to avoid food scarcity in the future. Non-ruminants, which would have been a panacea to this increased demand for animal-derived foods, have suffered from the rising costs of feed ingredient world-wide. The increase in the prices of conventional feedstuffs have attracted the attention of researchers on the potentials of lesser-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Such natural antimicrobials may also allow wildlife to recover from infections without medical intervention. Indeed, several studies have demonstrated their health and growth promotion benefits in domesticated animals (Abou‐Kassem et al, 2021 ; Ogbuewu et al, 2023 ; Rafeeq et al, 2022 , 2023 ) but there is no current comparable evidence for wildlife. Unfortunately, habitat degradation, climate change, pollution, intensive farming, and human encroachment are having a major influence on biodiversity including that of plants and microbes (Peixoto et al, 2022 ; Wang et al, 2018 ).…”
Section: Excluding Wildlife Could Limit Understanding Of and Action O...mentioning
confidence: 99%
“…Such natural antimicrobials may also allow wildlife to recover from infections without medical intervention. Indeed, several studies have demonstrated their health and growth promotion benefits in domesticated animals (Abou‐Kassem et al, 2021 ; Ogbuewu et al, 2023 ; Rafeeq et al, 2022 , 2023 ) but there is no current comparable evidence for wildlife. Unfortunately, habitat degradation, climate change, pollution, intensive farming, and human encroachment are having a major influence on biodiversity including that of plants and microbes (Peixoto et al, 2022 ; Wang et al, 2018 ).…”
Section: Excluding Wildlife Could Limit Understanding Of and Action O...mentioning
confidence: 99%
“…The plant is indigenous to Africa and other tropical countries [ 2 ]. Detailed information on the taxonomy and medicinal values of the plant has been documented in the literature [ 3 , 4 ]. Chemical profiling of Dialium bark meal indicates that it is rich in ash, fibre (i.e., lignin, cellulose, and hemicellulose), flavonoids, and total phenols [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on the taxonomy and medicinal values of the plant has been documented in the literature [ 3 , 4 ]. Chemical profiling of Dialium bark meal indicates that it is rich in ash, fibre (i.e., lignin, cellulose, and hemicellulose), flavonoids, and total phenols [ 2 , 4 , 5 ]. In addition, Dialium bark meal contains anti-nutritional factors (ANFs) like tannins, cyanogenic glycosides, and trypsin inhibitors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%